PERILAKU DEFORMASI PADA BENDUNGAN PIDEKSO - Noor Jakirin; Sukamta; Suprapto (LPPM Universitas Abdurrab, 2025)
Deformation monitoring is carried out during each stage of the dam's lifecycle, including the construction phase, initial reservoir filling, and the post-construction phase. The construction stage is particularly crucial, as rapid structural shifts may occur, which could compromise the dam's stability due to significant soil settlement or displacement. The Pidekso Dam, situated in Giriwoyo District, is a project initiated by the Ministry of Public Works and Housing (PUPR), with its planning process starting in 2015. Reservoir filling began on 14 October 2021. This study utilises a descriptive analysis method based on data from multilayer settlement instrument readings at the Pidekso Dam. The research aims to examine the deformation behaviour observed during the construction phase, as indicated by the instrument readings. Measurements taken between 21 July 2020 and 14 October 2021 at Sta +179.00 revealed a settlement of -3.091 mm during construction. At MS 8, the deformation was found to exceed normal limits.